EFEKTIVITAS METODE JARIMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG KELAS II SD NEGERI 0104 SIBUHUAN - Harahap, Nurhalimah; Daulay, Irma Sari; Tambunan, Miska Rizki (Journal Education Innovation (JEI), 2025)
This study aims to: (1) To determine the application of the jarimatika method in class II of SD Negeri 0104 Sibuhuan. (2) To determine the arithmetic ability of class II students of SD Negeri 0104 Sibuhuan. Based on the results of the study, it can be concluded that: (1) The arithmetic ability of class II students of SD Negeri 0104 Sibuhuan in the pre-cycle is still low. This can be seen from the results of observations that have been carried out, in the pre-cycle the average value of arithmetic ability obtained by students is 58.07, the arithmetic ability of students with the category "Not Good" is 5 students or 19%, the arithmetic ability of students with the category "Less Good" is 14 students or 54%, the arithmetic ability of students with the category "Good" is 5 students or 19% and the arithmetic ability of students with the category "Very Good" is 2 students or 8%. (2) The arithmetic ability of class II students of SD Negeri 0104 Sibuhuan in cycle I began to increase. This can be seen from the results of observations that have been carried out in cycle I, the average value of the students' numeracy ability is 68.08, the students' numeracy ability with the category "Not Good" is 2 students or 8%, the students' numeracy ability with the category "Less Good" is 8 students or 31%, the students' numeracy ability with the category "Good" is 12 students or 46% and the students' numeracy ability with the category "Very Good" is 4 students or 15%. In cycle II, it increased quite significantly, the average value of the students' numeracy ability was 76.15, the students' numeracy ability with the category "Not Good" was 1 student or 4%, the students' numeracy ability with the category "Less Good" was 4 students or 15%, the students' numeracy ability with the category "Good" was 14 students or 54% and the students' numeracy ability with the category "Very Good" was 7 students or 27%.